The role of e-procurement in promoting government transparency: Lessons from Surabaya - Novitaningrum, Badzlina Daroyani (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: This study examines accountability and transparency in the public procurement process, focusing on Surabaya, the first city to implement e-procurement reform. E-procurement leverages the latest information technology to improve procurement efficiency and transparency. Methods: A descriptive qualitative approach was used, using purposive sampling to gather in-depth insights from critical informants who thoroughly understood the research focus. Data were collected from various entities, including the Surabaya City Electronic Procurement Service (LPSE), the City Procurement Unit (ULP), and related public works and private auction companies. Findings: The implementation of e-procurement in Surabaya has succeeded in building an accountable and transparent system. This system has improved the procurement committee’s ability to justify and report the entire procurement process vertically to higher authorities and horizontally to the public. Despite this progress, some suppliers still engage in fraudulent practices, highlighting the need for continued vigilance and commitment. Conclusions: Although e-procurement has significantly improved accountability and transparency in the procurement process in Surabaya, the committee and suppliers need to uphold strong ethical standards to prevent fraud. The e-procurement system alone is not enough. This system must be supported by solid law enforcement and a commitment to integrity to fully realize its potential in creating a fair procurement environment. Novelty/Originality of this study: This study comprehensively evaluates e-procurement implementation in Surabaya, revealing improvements in accountability and transparency and remaining challenges. The findings offer an applicable model for other cities in Indonesia and developing countries to optimize public e-procurement systems.